Korelasi Nilai Hematokrit dan Jumlah Trombosit dengan Antibodi IgG dan IgM Dengue - Fadhila Az-Zahra; Meri Meri; Yosep Hadiansah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Dengue virus infection can affect blood cells, one of which is the number of platelets so that it decreases, due to the formation of viral antibody complexes that stimulate platelet aggregation. DHF is characterized by plasma leakage with an increase in hematocrit >20%. Diagnosis of dengue virus infection is supported by examination of IgG and IgM antibodies, platelet count, and hematocrit. The purpose of this study was to determine the correlation between hematocrit and platelet counts with IgG and IgM antibodies to DHF. Research method: cross-sectional. Laboratory data were processed using the SPSS Chi-Square test software. The results of the statistical test of the correlation between IgG/IgM antibody results with platelet count p = 0.375 and IgG/IgM antibody results on hematocrit p = 0.487 so that it has a significance value of > 0.05. Conclusion: there is no correlation between hematocrit value and platelet count with dengue IgG and IgM antibodies.